Identifikasi Minat dan Bakat Olahraga Menggunakan Metode Sport Search pada Siswa SMP di Panti Asuhan Muhammadiyah Ajibarang - Setiadi, Kelpin; Soenyoto, Tommy (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of the study: (1) to find out sports interests; (2) sports talents; (3) dominant sport talents and ; (4) the suitability between interests and talents of junior high school students. This research approach uses a quantitative descriptive method. The population in this study are junior high school students who lived in the Muhammadiyah Ajibarang orphanage. The sampling technique used was total sampling. The data collection techniques used in this research are (1) Questionnaire, (2) Sport Search test, (3) Documentation. From the results of data analysis obtained various kinds of sports interest in students which are influenced by intrinsic factors of 76.63% and extrinsic factors of 70.11%. There are various kinds of sports talent in students based on the talent of the athletic, martial, individual, racket, team, water and sports groups top 10 ranking. The dominant sport talents for students is diving. A total of 5 or 17.2% of students have a match between interests and talents, while 24 or 82.8% of students do not. The conclusion is that junior high school students who live in the Muhammadiyah Ajibarang Orphanage have various sports talents, but most of them of the potential is not in accordance with the interests of the students.